Le promontoire de la langue : variations sur une métaphore dans trois petits traités de Pascal Quignard - Cristina Álvares (Carnets)
In his petits traités, Pascal Quignard reflects on language in connection with the real, sex and nature. The topic I will address is the substantialist transformation of the perception of language through the metaphor of the tip of the tongue in the treatises published from 1993 (Le nom sur le bout de la langue) through 1995 (Rhétorique Spéculative): from form to substance, fainting to mastering, logos to physis. In this transformation, which also concerns the literary writing, Le sexe et l’effroi (1994), stressing the Ancient concept of phallos, is given a prominent role.